KAJIAN DAMPAK PEMBEBASAN LAHAN PEMBANGUNAN JARINGAN TRANSMISI LISTRIK TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT - Arifin Muhtar; Eka Intan Kumala Putri; Hariyadi Hariyadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Development of transmission line is needed to increase the availability of electrical demand. This development requires a land acquisition, which has some impacts toward socio-economic of society, namely changes of livehood and loss of earnings. Objectives of this study were: 1) to identify some problems caused by land acquisition; 2) to analyze the changes of livehood and income caused by land acquisition; 3) factors affected price of land compensation; 4) alternatives solution to minimize impact of land acquisition. The change of livehood was analyzed by descriptive qualitative method, meanwhile the change of income by loss of earning, factors affected price of land compensation by regression. This study was conducted in 12 villages in Bogor and Depok crossed by the transmission line. The result of study showed that the transmission lines development the emergencing of various problems, namely: (a) land acquisition is causing the loss of home for 3,33 percent of respondents that had to be relocated to other areas, (b) land acquisition is causing the loss of 16,63 percent agricultural land owned by community that affected by the transmission line, (c) land acquisition is causing internal conflict within the family of 5.00 percent respondents in terms of the distribution of compensation money received. The land acquisition causes change of livelihood of farmers (6,67 percent), owners of grocery shop and drink stalls business (3.33 percent), and business owners of rental house (3,33 percent). This causes loss of earning for 26.67 percent respondent, with the total loss of earnings of IDR 6,605,000 per month or an average of IDR 412,813 per month per respondent. The regression model of land compensation price has R-Square (adj) 73,9 percent, with the factors that significantly affect the value of land compensation are: Tax Object Sales Value (NJOP) of land, market price of the land, and the size area of respondents landholding, with a significance level of each respectively 0,000. The result of classical assumption test proves that the regression model is built in accordance with the rules of econometrics is good with no autocorrelation, no multicollinieraty, no heteroscedasticity, and the data is also distributed normally. To minimize the land acquisitioned impact should be noted about how the continuation of economic enterprise communities that rely on land as the main capital of the business, and how the compensation value specified must meet the aspect of obedience to the law and agreement with the land owners.Keywords: land acquisition, transmission line, livehood change, loss of earnings